1970
DOI: 10.3329/bjb.v36i2.1496
|View full text |Cite
|
Sign up to set email alerts
|

Micromorphology and anatomy of three <i>Symphytum</i> (Boraginaceae) taxa from Turkey

Abstract: Symphytum asperum Lepechin, S. ibericum Steven and S. sylvaticum Boiss. were examined morphologically, micromorphologically and anatomically. Scanning electron microscopy was used to examine leaf surface and trichomes of these species. These species had bifacial and hypostomatous leaf types. Epidermal cells of leaves were usually polygonal or irregular in form. The pattern of anticlinical cells may vary in different species and between the upper and lower epidermis of the same species. Stomata are anisocytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The analyzed plants developed bifacial leaves. This type of leaf blade was found in Boraginaceae species from the genera Heliotropium (Alwahibi and Bukhary, 2013), Pulmonaria (Gostin, 2009), Symphytum (Akçin and Baki, 2007), and Trachystemon (Akçin et al, 2004). Present investigations and literature data demonstrated that the palisade cells in Borago officinalis, B. pygmaea, and several other Boraginaceae species formed one or two layers (Selvi and Bigazzi, 2001;Gostin, 2009).…”
Section: Anatomical Structurementioning
confidence: 82%
See 1 more Smart Citation
“…The analyzed plants developed bifacial leaves. This type of leaf blade was found in Boraginaceae species from the genera Heliotropium (Alwahibi and Bukhary, 2013), Pulmonaria (Gostin, 2009), Symphytum (Akçin and Baki, 2007), and Trachystemon (Akçin et al, 2004). Present investigations and literature data demonstrated that the palisade cells in Borago officinalis, B. pygmaea, and several other Boraginaceae species formed one or two layers (Selvi and Bigazzi, 2001;Gostin, 2009).…”
Section: Anatomical Structurementioning
confidence: 82%
“…In Borago morissiana, anisocytic stomata were identified (Bigazzi and Ricceri, 1992). In turn, other Boraginaceae taxa exhibited both anomocytic and anisocytic stomata (Akçin, 2007;Zarinkamar, 2007;Akçin and Binzet, 2010), e.g., representatives of the genera Cynoglossum (Akçin, 2012), Moltkia (Doğu et al, 2012), and Symphytum (Akçin and Baki, 2007). Symphytum asperum had anomo-, aniso-, and diacytic stomata (Zarinkamar, 2007).…”
Section: Micromorphology Of the Epidermismentioning
confidence: 99%
“…Foliar anatomy of Heliotropium was also the subject of study by Abbasi et al (2011), Ahmed and Kordofani (2012), and Alwahibi and Bukhary (2013). Similarly, foliar anatomy was studied by Akc¸in and Baki (2007) in three Symphytum species, by Akc¸in et al (2012) in four Cynoglossum species, and by Gu¨ven et al (2013) in six Onosma species. Stomatal profile in the foliar epidermis was studied by Dasti et al (2003) in 31 species belonging to 15 genera, while foliar trichomes were extensively surveyed by Al-Nowaihi et al (1987), Selvi and Bigazzi (2001), Diane et al (2003), Taia (2006), Ventrella and Marinho (2008), Perveen (2009), and Mehrabian et al (2014).…”
Section: Introductionmentioning
confidence: 95%